Blockchain-based bilateral bidding market mechanism with carbon allocation on both supply and demand sides - Luo, Renjie; Wang, Hanyi; Deng, Hui; Jiang, Haiyang; Xu, Chengwei; Li, Zhiyi (Frontiers in Energy Research, 2022)
Recently, the interaction between power generation and load is continuously strengthened, which also provides a new method for realizing the decarbonization of the power system. This paper designs an auction method that enables a low-carbon economic dispatch, where the blockchain technology is employed to record the whole process data credibly. According to the regional division of market entities, carbon emissions are allocated to regions and entities by using the Owen value method. In order to reduce the expected carbon emission of entities, an additional carbon price is added to the original quotation through the allocation results. Case studies are conducted based on the typical output characteristics of wind and photovoltaic power generation in the wholesale market on an hourly basis. The results have validated the proposed method can facilitate the reduction of carbon emissions in the power system by giving priority to zero-carbon as well as low-carbon generation units.